Challenge: Financial education or survival (Research, Society and Development, 2022)
In the work, a research was carried out on the influence of Financial Education in the lives of high school students. The objective was divided into two stages: the first was to verify what makes people with similar financial conditions, some to live in goods and others not. The second is to verify how other people can be beneficiaries of Financial Education, even with low income. The research with the participants was of a qualitative-quantitative nature, carried out in the classroom, in a remote way, in the class of the 3rd Grade of the Technical Course in Agriculture and Livestock Integrated to High School, at the Federal Institute of Education, Science and Technology of Tocantins - IFTO, Campus Araguatins. Use of Financial Mathematics content: Percentage, Simple and Compound Interest, and Introduction to the family budget, as means and tools of control. The results obtained showed an importance of Financial Education in the discipline of Financial Mathematics. It appears that the Financial Education of the Individual and the Change of Attitude, also lead to Financial and Family Education. Thus, it can be seen that financial education can avoid indebtedness, in the same way as the opposite, leads the individual to financial lack, and later, to indebtedness.